Computational drug discovery of potential TAU protein kinase I inhibitors using in silico docking studies (Bangladesh Journal of Pharmacology, 2013)
The objective of the current study is to evaluate the tau protein kinase I inhibitory activity of flavonoids using in silico docking studies. In silico docking studies were carried out using AutoDock 4.2, based on the Lamarckian genetic algorithm principle. Memantine, a known neuro-receptor antagonist is currently used in the treatment of Alzheimer's disease. The results showed that all the selected flavonoids showed binding energy ranging between -7.07 kcal/mol to -4.85 kcal/mol when compared with that of the standard  (-5.89 kcal/mol). Inhibition constant (6.62 µM to 280.05 µM) and intermolecular energy (-9.45 kcal/mol to -6.64 kcal/mol) of the ligands also coincide with the binding energy. These molecular docking analyses could lead to the further development of potent tau protein kinase I inhibitors for the treatment of Alzheimers disease. Further investigations on the above compounds and in vivo studies are necessary to develop potential chemical entities for the prevention and treatment of Alzheimer's disease.